What Is Wellbeing, and What Is Important for Wellbeing? Indigenous Voices from across Canada - Stephen R. J. Tsuji; Aleksandra M. Zuk; Andrew Solomon; Ruby Edwards-Wheesk; Fatima Ahmed; Leonard J. S. Tsuji (International Journal of Environmental Research and Public Health, 2023)
Indigenous peoples’ perceptions of wellbeing differ from non-Indigenous constructs. Thus, it is imperative to recognize that Indigenous peoples will conceptualize wellbeing from their perspectives and set their own wellbeing priorities. In keeping with this viewpoint, the aims of the present study were to conceptualize wellbeing and determine what was (and is) important for wellbeing from Canadian Indigenous peoples’ perspectives. In this paper, we take a partnership approach based on the elements of respect, equity, and empowerment. One primary data source and two existing data sources were examined and analyzed thematically utilizing a combination approach of deductive and inductive coding. Indigenous leadership and organizations viewed wellbeing holistically and conceptualized wellbeing multidimensionally. From across Canada, wellbeing was communicated as physical, economic, political, social, and cultural. The scaling of wellbeing represented a collectivist perspective, and land was the connecting thread between all types of wellbeing, being a place to practice cultural traditions, reassert one’s Indigenous identity, find solace, and pass on Indigenous knowledge and languages. Although wellbeing was discussed in the context of the individual, family, community, and nation, wellbeing was most often discussed at the cultural level by regional and national Indigenous leadership and organizations. Even in acknowledging the great cultural diversity among Canadian Indigenous nations, four concordant themes were identified regionally and nationally, with respect to what was important for cultural wellbeing: land and water, sustainability, and inherent obligations; being on the land, and indigenous languages and knowledge systems; sustainable development; and meaningful involvement in decision-making, and free, prior, and informed consent. Taking into account these themes is foundational for any interaction with Indigenous peoples, especially in the context of land, culture, and development. There needs to be a new ...